2023
DOI: 10.1002/ejic.202300102
|View full text |Cite
|
Sign up to set email alerts
|

Deep Red Emitting Heteroleptic Ir(III) Complexes that Incorporate Unsymmetrical 4‐quinoline Carboxylic Acid Derived Ligands

Abstract: Six disubstituted ligands based upon 2‐(2′‐pyridinyl/pyrazinyl)quinoline‐4‐carboxylic acids have been synthesised, solvent‐free, in one step from a range of commercially available isatin derivatives. These species behave as ancillary chelating ligands for Ir(III) complexes of the form [Ir(C^N)2(N^N)]PF6 (where C^N=cyclometalating ligand; N^N=2‐(2′‐pyridinyl/pyrazinyl)quinoline‐4‐carboxylic acids). An X‐ray crystallographic study on one complex shows a distorted octahedral geometry wherein a cis‐C,C and trans‐N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 82 publications
(55 reference statements)
1
3
0
Order By: Relevance
“…The bond lengths and bond angles that describe the distorted octahedral coordination sphere are closely comparable with little variance induced by the addition of cationic imidazolium units (crystal structure metrics can be found in the ESI Tables S1–S3†). In fact, these structural parameters are very closely comparable to previous relevant examples, 23 including those based upon this type of 2-phenylquinoxaline cyclometalating ligand at Ir( iii ). 24…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The bond lengths and bond angles that describe the distorted octahedral coordination sphere are closely comparable with little variance induced by the addition of cationic imidazolium units (crystal structure metrics can be found in the ESI Tables S1–S3†). In fact, these structural parameters are very closely comparable to previous relevant examples, 23 including those based upon this type of 2-phenylquinoxaline cyclometalating ligand at Ir( iii ). 24…”
Section: Resultssupporting
confidence: 84%
“…Single crystals suitable for X-ray crystallographic studies were obtained for the [Ir(Me 3 quinox) 2 (MeCN) 2 ]BF 4 precursor and [Ir Scheme 1 Structures of the N-methyl imidazolium functionalised monometallic Ru(II) and Ir(III) complexes (black) synthesised in this study, together with relevant reference compounds (grey). relevant examples, 23 including those based upon this type of 2-phenylquinoxaline cyclometalating ligand at Ir(III). 24 Reactions with AuCl(PPh 3 ): synthesis and characterisation of the heterometallic complexes (structures shown in Scheme 2).…”
Section: Single Crystal X-ray Diffractionmentioning
confidence: 99%
“…This assignment of origin is consistent with that reported for similar complexes in the literature. 21 Additionally, these data clearly showed that the charge of complexes influences the emission maximum promoting a shift from less energetic in neutral species ( 1 ) to more energetic emission in cationic species ( 2 ) as a consequence of changes in the energy of frontier orbitals. In this particular case, it can be proposed that protonation of the pyridylpyrazol renders less electron density on the Ir III metal center, lowering the energy of the HOMO orbitals 22 and blue-shifting the emission maxima from 720 to 690 nm.…”
Section: Resultsmentioning
confidence: 86%
“…Cyclometalated Ir(III) complexes continue to attract great attention due to their facile chemical modifications, readily tunable photophysical and structural properties, and their high stability. [1][2][3][4][5][6][7][8][9][10] In contrast to the extensive development of monoiridium complexes that followed the initial work by Watts and co-workers in the 1980s, [11] diiridium complexes have been largely neglected, although the bridging ligand can impart additional interesting structural and electronic variations compared to monoiridium systems. [12,13] Diiridium complexes are often obtained as a mixture of diastereomers, which are generally not separated.…”
Section: Introductionmentioning
confidence: 99%